Climate vulnerability and socio-environmental situation: perceptions in a semiarid region of northeastern Mexico - López-García, Thania Gabriela; Manzano, Mario G. (Instituto de Ecología, A.C., 2016)
Interactions of climate and natural resources with environmental and social deterioration are analyzed in this study of an arid region of northern Mexico known as Galeana Valley. The story of the social development of the region was constructed through face-to-face interviews. The perceptions of farmers regarding vulnerability to climate change, water use and the possibility of adaptation were also analyzed. The main problems in the region arising from the analysis are drought and the depletion of hydrological resources, for which the aquifers are the only source of supply. The importance of direct sources of information and interaction with local stakeholders for creating diagnostics, aligning assistance and agendas of rural development is discussed.